A PCF-SPR Refractive Index Sensor Excited by HE1,1 Mode - LIU Chao; FU Hai-hao; LU Jing-wei; WANG Jian-xin (Journal of Harbin University of Science and Technology)
With the continuous development of optical fiber sensing technology， photonic crystal fiber (PCF) sensors based on surface plasmon resonance (SPR) have become a hot spot in the current sensing field. At present， the modes for exciting SPR are mainly LP0,1， and there are few studies on PCF sensors using orbital angular momentum (OAM) mode to excite SPR. A PCF sensor with SPR excited by the fundamental mode (HE1,1 mode) of OAM is proposed by finite element simulation， and its phase matching， wavelength sensitivity， FOM and other properties are studied. Numerical results indicate that the SPR sensor can detect analytes with a refractive index in the range of 1.29~1.37， the maximum wavelength sensitivity is 10,000 nm/RIU， and the FOM is as high as 200.89 RIU-1 . In addition， using the gold dielectric filling method to replace the traditional coating process reduces the fabrication difficulty of the sensor. The PCF-SPR sensor has great applications in safety monitoring， oil logging， and so on.